“Tumor immunology meets oncology” (TIMO), 18 April–20 April 2024, in Brandenburg an der Havel, Germany - Barbara Seliger (Cancer Immunology, Immunotherapy)
Abstract The TIMO meeting XVIII 2024 covered both basic and translational tumor immunological topics, which were presented by national and international scientists and clinicians.